Implementation Of Khiyar On Ba'i Salam Transactions In Student Cooperative At Islamic Boarding School Darussalam Gontor For Girl 2 According To Fiqh Muamalah - Daud Sukoco; Zulfatus Sa'diah; Aqif Khilmia (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2022)
Abstract Basically, buying and selling transactions in determining the contract, the party who transacts has the right to continue or cancel a contract. A solution in Islam, offering the right of khiyar. The purpose of this study was to determine the implementation of Khiyar in Ba'i Salam transactions at the Student Cooperative Store and to review it from the perspective of muamalah fiqh. The conclusion is that in the practice of ba’I salam carried out by the Gontor Putri 2 student cooperative with distributors, they have implemented khiyar aib, khiyar ru’yah, and khiyar syarat. When viewed from the point of view of fiqh muamalah, the application of khiyar aib is appropriate, because there was a new defect known to the buyer after the contract was made and before the receipt. khiyar aib is still allowed in muamalah fiqh because khiyar aib does not prevent the perfection of the handover of goods. However, the actual khiyar ru’yah, and khiyar syarat in ba'i salam are not necessary, because if the order has the right of the khiyar, then the goods will be borne by the seller, and so on, it is enough just to mention the specifications of the goods for the validity of the salam contract. Keywords: Khiyar, Ba’i Salam